Sterile Pyuria: Causes and Evaluation - Roy, Jaba; Hassan, Munir; Nag, Dipankar Chandra (Journal of Dhaka National Medical College & Hospital, 2016)
Abstract Not Available. J. Dhaka National Med. Coll. Hos. 2016; 22 (02): 51-55